The Correlation between Occupation and Birth Interval in Primary Postpartum Hemorrhage - Nur Reski Annisa; Nadjamuddin; Rahadi Arie Hartoko; Sari Ifdiana Jalal (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
ntroduction: Postpartum hemorrhage stands as one of the major contributors to maternal mortality globally. Postpartum hemorrhage is a rapid heavy vaginal bleeding that can cause signs and symptoms of hypovolemic shock. Many factors cause postpartum hemorrhage classified into indirect causes, namely type of delivery, age, parity, birth spacing, family income, education, and occupation. Objective: This study aims to determine the correlation between occupation and birth spacing with primary postpartum hemorrhage. Method: This study uses a case-control approach with a purposive sampling technique. The sample for this study included multigravida mothers and mothers diagnosed with primary postpartum hemorrhage at Ananda Maternity and Child Hospital, Makassar, in 2021. The total sample was 174 consisting of 84 cases and 84 control samples. The research instrument data is in the form of secondary data, namely medical records. Data analysis employed the chi-square test for bivariate analysis and multiple logistic regression for multivariate analysis, with a significance level of 0.05 Result: The results of the bivariate analysis showed a relationship between occupation (p-value: 0.000) and delivery distance (p-value: 0.000). Working mothers are 6 times at risk for experiencing primary postpartum hemorrhage (OR= 5.833) while mothers whose delivery interval is < 2 years or > 5 years have 4 times the risk (OR= 3.719). The results of the multivariate analysis show that the work and pregnancy distance is significantly related to the risk of postpartum hemorrhage (value P: 0,000) where the odds ratio for work (OR = 6,178) is higher than the distance of pregnancy (OR = 4.008). Conclusion: Occupational factors and birth spacing are significantly associated with primary postpartum hemorrhage, working mothers have a higher risk of experiencing primary postpartum hemorrhage. Pregnant women and women of childbearing age should receive more education about postpartum hemorrhage and its influencing factors to help prevent and identify it early.